1988
DOI: 10.1530/jrf.0.0840089
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of embryo-derived platelet-activating factor prevent implantation of mouse embryos

Abstract: Summary. Inhibitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Similarly, significantly inhibited the direct effects of exogenous PAF on the oxidative metabolism of lactate and glucose by 2-cell mouse embryos during culture in vitro (Ryan et ai, 1990). (Spinks & O'Neill, 1988) and the observed effect of exogenous PAF in enhancing the implantation potential of cultured embryos.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, significantly inhibited the direct effects of exogenous PAF on the oxidative metabolism of lactate and glucose by 2-cell mouse embryos during culture in vitro (Ryan et ai, 1990). (Spinks & O'Neill, 1988) and the observed effect of exogenous PAF in enhancing the implantation potential of cultured embryos.…”
Section: Resultsmentioning
confidence: 89%
“…It has been suggested that embryo-derived PAF activity is necessary for successful implantation (Spinks & O'Neill, 1988) and that its site of action is at the embryonic level (Ryan et ai, 1989;Ryan et ai, 1990;Spinks et ai, 1990). In view of the reduced secretion of embryo-derived PAF after in-vitro culture (Ryan et ai, 1989), PAF may be a limiting factor in maintaining embryo viability during culture in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…1-O-alkyl-2-acetyl-sn-glyceryl-3-phosphocholine (platelet-activating factor, PAF) was the first characterized factor released by the preimplantation embryo to be identified (O'Neill, 1985a;O'Neill, 1985b). It was subsequently shown that PAF also stimulated embryo metabolism , cell cycle progression (Roberts et al, 1993) and embryo viability Spinks and O'Neill, 1988;Spinks et al, 1990), thereby providing evidence for an autocrine loop in the early embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of rodents during early pregnancy with a range of PAF-receptor antagonists reduced the incidence of successful implantation [9][10][11][12][13]. However, the failure of some investigators [14] to observe this effect, and the discovery by others [15] that the effective dose range of antagonists was very narrow, called into question the nature of the PAF receptor present in the early embryos.…”
Section: Introductionmentioning
confidence: 99%